Molecular dynamics simulations of the bacterial outer membrane protein FhuA: a comparative study of the ferrichrome-free and bound states. - Faraldo-Gómez, J; Smith, G; Sansom, MS (2003)
FhuA is one of the more complex members of the superfamily of bacterial outer membrane proteins. Its primary function is to provide a binding site on the outer membrane surface for siderophores, such as ferrichrome, and subsequently to facilitate their energy-dependent transport across the membrane, presumably powered by the TonB-ExbBD protein complex that resides in the cytoplasmic membrane. Crystal structures of FhuA with and without a bound ferrichrome molecule have provided some clues as to the initial stages of the siderophore transport mechanism. In the current study, we have employed 10-ns duration molecular dynamics simulations of FhuA and of the FhuA-ferrichrome complex, both embedded in a phospholipid bilayer, to probe the short timescale dynamics of this integral membrane protein, and to explore possible mechanistic implications of this dynamic behavior. Analysis of the dynamics of the protein suggests that the extracellular loops move as relatively rigid entities relative to the transmembrane beta-barrel. Comparison of the two simulations (with and without bound ferrichrome) revealed some ligand-induced changes in loop mobility. Specifically, loop L8 appears to be involved in a mechanism whereby the binding site is gated closed upon ligand binding. Analysis of the dynamics of water molecules within the core of the FhuA protein provided no evidence for a water-permeable protopore through which the ferrichrome might pass without a major perturbation of the FhuA protein. Overall, these simulations support the proposal that binding of ferrichrome initiates a signaling mechanism that ultimately leads to the TonB-mediated partial or total removal of the core domain from the beta-barrel, thus opening up a permeable pore. These simulations are among the longest that have been performed on a complex membrane protein. However, a simple analysis of sampling reveals that the description of protein motions is far from complete.